Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's analyze each expression step-by-step and compare them:
1. Expression: [tex]\( \frac{3^3}{3} \)[/tex]
[tex]\[ = 3^{3-1} \quad \text{(Subtract the exponents since the bases are the same)} = 3^2 \][/tex]
2. Expression: [tex]\( \frac{3^{-3}}{3^4} \)[/tex]
[tex]\[ = 3^{-3-4} \quad \text{(Subtract the exponents)} = 3^{-7} \][/tex]
3. Expression: [tex]\( \frac{3^7}{3^0} \)[/tex]
[tex]\[ = 3^{7-0} \quad \text{(Any number to the power of zero is 1, so 3^0 = 1)} = 3^7 \][/tex]
4. Expression: [tex]\( 3 \times 3^6 \)[/tex]
[tex]\[ = 3^1 \times 3^6 \quad \text{(Since 3 is the same as 3^1)} = 3^{1+6} \quad \text{(Add the exponents because the bases are the same)} = 3^7 \][/tex]
5. Expression: [tex]\( 3^3 \times 3^4 \)[/tex]
[tex]\[ = 3^{3+4} \quad \text{(Add the exponents because the bases are the same)} = 3^7 \][/tex]
Now, comparing each of these simplified forms:
- [tex]\( \frac{3^3}{3} = 3^2 \)[/tex]
- [tex]\( \frac{3^{-3}}{3^4} = 3^{-7} \)[/tex]
- [tex]\( \frac{3^7}{3^0} = 3^7 \)[/tex]
- [tex]\( 3 \times 3^6 = 3^7 \)[/tex]
- [tex]\( 3^3 \times 3^4 = 3^7 \)[/tex]
We observe that all the expressions except for the second one ([tex]\( \frac{3^{-3}}{3^4} \)[/tex]) are equal to [tex]\( 3^7 \)[/tex] or can be simplified to [tex]\( 3^7 \)[/tex].
Thus, the expression that is not equal to the others is the second one: [tex]\( \frac{3^{-3}}{3^4} \)[/tex].
Therefore, the expression that is not equal to the others is:
Option 2: [tex]\( \frac{3^{-3}}{3^4} \)[/tex]
Hence, the expression which is not equal to the others is the second one, or equivalently, the answer is:
### 2
1. Expression: [tex]\( \frac{3^3}{3} \)[/tex]
[tex]\[ = 3^{3-1} \quad \text{(Subtract the exponents since the bases are the same)} = 3^2 \][/tex]
2. Expression: [tex]\( \frac{3^{-3}}{3^4} \)[/tex]
[tex]\[ = 3^{-3-4} \quad \text{(Subtract the exponents)} = 3^{-7} \][/tex]
3. Expression: [tex]\( \frac{3^7}{3^0} \)[/tex]
[tex]\[ = 3^{7-0} \quad \text{(Any number to the power of zero is 1, so 3^0 = 1)} = 3^7 \][/tex]
4. Expression: [tex]\( 3 \times 3^6 \)[/tex]
[tex]\[ = 3^1 \times 3^6 \quad \text{(Since 3 is the same as 3^1)} = 3^{1+6} \quad \text{(Add the exponents because the bases are the same)} = 3^7 \][/tex]
5. Expression: [tex]\( 3^3 \times 3^4 \)[/tex]
[tex]\[ = 3^{3+4} \quad \text{(Add the exponents because the bases are the same)} = 3^7 \][/tex]
Now, comparing each of these simplified forms:
- [tex]\( \frac{3^3}{3} = 3^2 \)[/tex]
- [tex]\( \frac{3^{-3}}{3^4} = 3^{-7} \)[/tex]
- [tex]\( \frac{3^7}{3^0} = 3^7 \)[/tex]
- [tex]\( 3 \times 3^6 = 3^7 \)[/tex]
- [tex]\( 3^3 \times 3^4 = 3^7 \)[/tex]
We observe that all the expressions except for the second one ([tex]\( \frac{3^{-3}}{3^4} \)[/tex]) are equal to [tex]\( 3^7 \)[/tex] or can be simplified to [tex]\( 3^7 \)[/tex].
Thus, the expression that is not equal to the others is the second one: [tex]\( \frac{3^{-3}}{3^4} \)[/tex].
Therefore, the expression that is not equal to the others is:
Option 2: [tex]\( \frac{3^{-3}}{3^4} \)[/tex]
Hence, the expression which is not equal to the others is the second one, or equivalently, the answer is:
### 2
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.